The attitude of banking institutions towards hiring gay applicants - Secular, Roberto Jr. D.
The issue of hiring homosexuals is one hardly ever discussed openly in some Filipino organizations. This study, then, seeks to determine the attitude of banking institutions towards hiring gay applicants. This is based on the concept that the decisions of the hiring committee/personnel manager is affected by his/her perception of gays. This study was conducted in Iloilo City proper with the hiring committee/personnel managers of the different banks having a localized hiring process. Only nineteen (19) of them, however, responded to the survey. The questionnaires were the only instrument employed by the researchers to gather data. With the data gathered, the researchers analyzed them using the frequency and percentage distribution. The results and findings were presented according to how they answer the objectives set by the researchers. Based on the findings of the study, the attitudes of banking institution toward gays does not significantly affect their decision in the hiring process.